Six species of Psilanthus transferred to Coffea (Coffeeae, Rubiaceae) - Davis, A. P. (Phytotaxa, 2014)
The placement of Psilanthus into the synonymy of Coffea necessitates nomenclatural changes. Five new combinations and two new names are provided: C. bengalensis var. bababudanii, C. brassii, C. malabarica, C. neobridsoniae, C. neoleroyiana, C. sapinii and C. semsei.